Unraveling The Feasibility of Health and Wellness Food Business Through a Financial Perspective : A Case Study of Asa Cerra - Fakhira Elda Khairunnisa; Irawan, Atika (Journal Integration of Social Studies and Business Development, 2024)
Asa Cerra is positioning itself to meet the growing global demand for health-conscious and sustainable products. Its flagship offering, "Nata De Whey," is a probiotic-rich beverage crafted from whey waste from mozzarella cheese. This product not only aims to enhance health but also to support environmental sustainability. Despite favorable initial feedback, a comprehensive financial feasibility study had yet to be conducted to ensure long-term viability. This research addresses this gap by evaluating Asa Cerra's financial feasibility using a combination of primary data from the company and secondary data from similar industry players. The study employs key financial metrics, including Payback Period, Net Present Value (NPV), and Internal Rate of Return (IRR). It integrates scenario analysis to capture a range of potential outcomes: most likely, pessimistic and optimistic. The analysis reveals a promising financial outlook for Asa Cerra, with a payback period of 2.4 years, an NPV of Rp465,551,298, and an IRR of 38.29%, significantly exceeding the Weighted Average Cost of Capital (WACC) of 9.00%. These results suggest that Asa Cerra is financially sound and has the potential for sustainable growth. The comprehensive financial assessment supports Asa Cerra's strategic planning efforts and highlights its readiness for long-term success in the market.